Club convergence analysis of city-level electricity consumption in Turkey. (15th February 2023) - Taştan, Hüseyin; Yıldız, Hakan
Abstract: This study examines the presence of convergence clubs in per capita electricity consumption across cities in Turkey over the period 2000–2020. Using the Phillips-Sul club convergence test and the clustering algorithm, we explore whether total, industrial, and residential electricity consumption across regions converge to the same long-run equilibrium or diverge. We also analyze the drivers of the club formation after identifying convergence clubs using ordered logit regressions. The findings support the full convergence in residential consumption while separate clubs with different convergence dynamics and steady-state levels are identified in industrial and total electricity consumption. Results indicate that there are two convergence clubs in total electricity consumption which may be clustered as high and low consumption regions. Our analysis also identifies two clusters in industrial consumption with a dominating club. Results from the ordered logit analysis suggest that income, industrial activities, and international trade are positively associated with club formation in total electricity consumption. Overall, our findings suggest that energy policies need to be tailored and implemented on a regional and sectoral basis since energy user groups have heterogeneous convergence behavior. Highlights: The convergence hypothesis in electricity consumption across Turkish cities. The presence of club convergence is analyzed using the Phillips and Sul algorithms. Found two clubs in industrial and total use and one club in the residential sector. An ordered logit analysis is performed to identify the drivers of club membership. Energy policies need to be tailored and implemented on a regional basis.